2019
DOI: 10.15575/psy.v6i1.4082
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Psychological Well-Being of Rural Poor School Students In Sabah, Malaysia

Abstract: Mental health disorders are major causes of disability to those affected, their families and the wider society. Absence of mental illness, or ambitiously, the presence of psychological well-being is key to the optimal functioning of individuals, for them to lead fuller lives and essential for them to contribute actively to society. Some studies have explored the links between psychological well-being and emotional intelligence. However, no such study has focussed on rural, and more often than not, poor student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
1
5
0
3
Order By: Relevance
“…Therefore, the responses summarize Goleman's (1995) statement that emotional self-awareness is to have a complete idea of all one's strengths, weaknesses, and needs and understanding that these characteristics affect others as well as oneself. The findings are consistent with Malinauskas and Malinauskiene (2020), Mehmood and Gulzar, (2014), and Rathakrishnan (2019) which demonstrate that the ability to recognize and manage emotions could contribute to an increase in well-being.…”
Section: Emotional Awarenesssupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, the responses summarize Goleman's (1995) statement that emotional self-awareness is to have a complete idea of all one's strengths, weaknesses, and needs and understanding that these characteristics affect others as well as oneself. The findings are consistent with Malinauskas and Malinauskiene (2020), Mehmood and Gulzar, (2014), and Rathakrishnan (2019) which demonstrate that the ability to recognize and manage emotions could contribute to an increase in well-being.…”
Section: Emotional Awarenesssupporting
confidence: 89%
“…3( 4)-2021 regulation of emotional intelligence. Furthermore, a crosssectional study that looked at the relationship between emotional intelligence and psychological well-being of rural students in Sabah, Malaysia, showed that emotional intelligence could predict psychological well-being (Rathakrishnan et al, 2019). This indicates that capacities of emotional intelligence predict aspects related to personal well-being and a positive relation between life satisfaction and subjective happiness (Guerra-Bustamante et al, 2019; Rathakrishnan et al, 2019).…”
Section: Journal Of Humanities and Education Development (Jhed)mentioning
confidence: 99%
“…Adults also need a lot of exposes to COVID-19 pandemic and how they can protect themselves ( Rathakrishnan and Alfred, 2013 ). Adults who staying in rural area more are affected by their psycho well-being and mental health especially on COVID-19 pandemic ( Rathakrishnan et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…This condition is referred Adults also need a lot of exposes to COVID-19 pandemic and how they can protect themselves (Rathakrishnan and Alfred, 2013). Adults who staying in rural area more are affected by their psycho well-being and mental health especially on COVID-19 pandemic (Rathakrishnan et al, 2019). Finally, the fourth hypothesis found spirituality significantly mediated the relationship between fear of COVID-19 and mental health.…”
Section: Relationship Between Fear and Mental Healthmentioning
confidence: 92%
“…En Malasia se ha encontrado que Alamo, K., Bienestar Psicológico E Inteligencia Emocional En Mujeres Víctimas De Violencia De La Unidad De Medicina Legal Ii Ancash -2022Rev. PAIAN 2022 la inteligencia emocional podía predecir el bienestar psicológico de una persona, debido a que mediante el análisis de datos se observó una correlación de 0.430 y una significancia de 0.001<0.05 (Rathakrishnan et al, 2019). A nivel nacional destacan los trabajos de García et al (2021) quienes han encontrado que la inteligencia emocional es un predictor significativo del bienestar psicológico y sus dimensiones ya que mediante las regresiones lineales se obtuvo un R 2 -Cox = 0,52, R 2 -Nagelkerke = 0,71, 87,16% de clasificación correcta total; otros estudios al analizar las virtudes, el bienestar psicológico y la resiliencia en jóvenes, han reportado que estas variables tienen una asociación de 0.70 a 0.87, se encontró a que la trascendencia, humanidad y sabiduría, fueron predictores de bienestar; y una mayor resiliencia reportada conduce a un mayor bienestar, encontraron que virtudes se asociaron diferencialmente con el bienestar, la humanidad era un predictor significativo a través de la ciudadanía cultural y el compromiso social, una mayor resiliencia se correlacionó con una mayor bienestar (Inoñan, 2020).…”
Section: -Introducciónunclassified